Association between soluble neprilysin and diabetes: Findings from a prospective longitudinal study - Hu, Junting; Zhu, Hanyun; Dai, Yunlang; Liu, Yang; Lu, Ying; Zhu, Shasha; Chen, Linan; Zhang, Mingzhi; Jiang, Tingbo; Peng, Hao (Frontiers in Endocrinology, 2023)
Background The potential role of neprilysin (NEP) in glucose metabolism has been found by basic studies but lacks population evidence. The objective of this study was to examine the association between serum NEP and diabetes in Chinese adults. Methods In a prospective longitudinal cohort study – the Gusu cohort (n=2,286, mean age: 52 years, 61.5% females), the cross-sectional, longitudinal, and prospective associations between serum NEP and diabetes were systemically examined by logistic regression adjusting for conventional risk factors. Serum NEP was measured at baseline using commercial ELISA assays. Fasting glucose was repeatedly measured 4 years apart. Results The cross-sectional analysis found a positive association between serum NEP and fasting glucose at baseline (β=0.08, P=0.004 for log-transformed NEP). This association persisted after controlling for the dynamic risk profiles during follow-up (β=0.10, P=0.023 for log-transformed NEP). The prospective analysis found that a higher level of serum NEP at baseline was associated with a higher risk of diabetes during follow-up (OR=1.79, P=0.039 for log-transformed NEP). Conclusions Serum NEP was not only associated with prevalent diabetes but also predicted the future risk of diabetes development in Chinese adults, independent of many behavioral and metabolic factors. Serum NEP may be a predictor and even a new therapeutic target for diabetes. However, the casualty and mechanisms of NEP in the development of diabetes require further investigation.